Algerian Cultural Imprints In The Levant Between The Two Centuries19-20m - Sebgag, Tahar (جامعة الوادي - University of Eloued, 2024)
The historical relations between the two basins of the Mediterranean, the West and the East, are very ancient, first by virtue of the presence of holy places in the East for Muslims. Therefore, we see Moroccans and others often traveling there to visit those places for essentially religious motives, and for various other motives such as the pursuit of knowledge, trade, tourism, and others. Most of the immigrants went to the country of Hijaz to perform the Hajj and Umrah rituals and see the major shrines. Others went there with the intention of seeking knowledge or obtaining jurisprudential licenses from some of the leading Islamic scholars and jurists settled there, while some of the Algerian immigrants headed to Egypt and the Levant to see other shrines. To increase knowledge, culture and practice trade. Wherever these immigrants went, they left their mark in various fields and fields, especially intellectual, cultural, military, and judicial
مقال
Keywords: Levant, Interaction, Maghrebians, Immigrants, Palestine, Syria, Algeria